Position of theme in Czech and English academic texts - Brisudová, Pavla (Univerzita Pardubice, 2011)
The aim of this paper is to investigate the position of theme in Czech and English academic text. This work is divided into a theoretical and a practical part. In the theoretical part the Czech and English word order and its function is described. Further theme and its position are discussed. In the practical part the English academic text and its Czech translation was analyzed. One hundred sentences were chosen from the both texts. The position of the theme, its expressing by sentence elements and its realization by word classes and phrases were studied in this corpus. After that the differences and common features in both languages were detected. The results were summarized in tables and graphs and subsequently they were interpreted regarding to the academic style.
Pozice tématu v českých a anglických akademických textech
Keywords: slovosled; funkční větná perspektiva; téma; akademický styl; word order; functional sentence perspective; theme; academic style